Becoming a new kind of professional: a black woman academic caught in a transition - MOHOPE, SEBOLAI SOPHIE (South African Journal of Higher Education, 2016)
The post-1994 democracy in South Africa sought new policies to steer higher education institutions (HEIs) towards transformation, intended to end the segregation policies of apartheid. Although certain policies led to higher institutions opening their doors to students and staff from different backgrounds and institutions, the legacy of apartheid remained to haunt, overtly and covertly, black woman academics, amongst others, as they attempted to pursue their teaching and research identities in these new contexts. It is against this background that I explore my personal experiences as a black academic, using an auto-ethnographic qualitative method, to reveal “sensitive issues and innermost thoughts” that are not normally within reach (Chatham-Carpenter, as cited in Ngunjiri, Hernandez and Chang 2010, p. 17). I explore my professional position and experiences within higher institutions, as these institutions grappled with issues of transformation. I describe what is was like being part of the process of moving from one university which had been reserved for black people to another, one that was then a ‘white’ higher institution. I explore how my teacher training in a ‘blacks only’ University led to the kinds of knowledge and practices that in my new context either enabled or constrained my advancement. I then question the lack of mentorship in these new contexts. I conclude by reflecting on how these experiences may assist a new generation of black women academics and help support transformation goals for higher education institutions in general. Keywords: organisational change; mentorship, community of practice, institutional transformation